Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's start with the equation [tex]\(\log_6 x + \log_6 (x+5) = 2\)[/tex].
### Step-by-Step Solution:
1. Combine the logarithmic terms:
[tex]\[ \log_6 x + \log_6 (x+5) = \log_6 [x \cdot (x+5)] \][/tex]
This uses the logarithmic property: [tex]\(\log_b a + \log_b c = \log_b (a \cdot c)\)[/tex].
2. Simplify the equation:
[tex]\[ \log_6 [x \cdot (x+5)] = 2 \][/tex]
3. Convert the logarithmic equation to an exponential equation:
If [tex]\(\log_b a = c\)[/tex], then [tex]\(a = b^c\)[/tex]. Applying this property:
[tex]\[ x \cdot (x+5) = 6^2 \][/tex]
4. Simplify further:
[tex]\[ x(x + 5) = 36 \][/tex]
[tex]\[ x^2 + 5x - 36 = 0 \][/tex]
5. Solve the quadratic equation:
To solve the quadratic equation [tex]\(x^2 + 5x - 36 = 0\)[/tex], we can use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = 5\)[/tex], and [tex]\(c = -36\)[/tex].
Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = 5^2 - 4 \cdot 1 \cdot (-36) \][/tex]
[tex]\[ \Delta = 25 + 144 \][/tex]
[tex]\[ \Delta = 169 \][/tex]
Find the roots:
[tex]\[ x = \frac{-5 \pm \sqrt{169}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-5 \pm 13}{2} \][/tex]
This gives us two solutions:
[tex]\[ x_1 = \frac{-5 + 13}{2} = \frac{8}{2} = 4 \][/tex]
[tex]\[ x_2 = \frac{-5 - 13}{2} = \frac{-18}{2} = -9 \][/tex]
6. Check the solutions:
We must validate that they are within the domain of the original logarithmic function. Logarithms are defined for positive real numbers.
- For [tex]\(x = 4\)[/tex]:
Both [tex]\( \log_6 x = \log_6 4 \)[/tex] and [tex]\( \log_6 (x+5) = \log_6 9 \)[/tex] are defined.
- For [tex]\(x = -9\)[/tex]:
[tex]\(\log_6 (-9)\)[/tex] is not defined because the logarithm of a negative number is not a real number.
7. Identify valid solutions:
From the initial options [tex]\(-12, -9, 4, 32, 36\)[/tex], we see that the valid solution [tex]\(x = 4\)[/tex] is within these options.
### Conclusion:
The potential solution for the equation [tex]\(\log_6 x + \log_6 (x+5) = 2\)[/tex] from the given options is:
[tex]\[ x = 4 \][/tex]
### Step-by-Step Solution:
1. Combine the logarithmic terms:
[tex]\[ \log_6 x + \log_6 (x+5) = \log_6 [x \cdot (x+5)] \][/tex]
This uses the logarithmic property: [tex]\(\log_b a + \log_b c = \log_b (a \cdot c)\)[/tex].
2. Simplify the equation:
[tex]\[ \log_6 [x \cdot (x+5)] = 2 \][/tex]
3. Convert the logarithmic equation to an exponential equation:
If [tex]\(\log_b a = c\)[/tex], then [tex]\(a = b^c\)[/tex]. Applying this property:
[tex]\[ x \cdot (x+5) = 6^2 \][/tex]
4. Simplify further:
[tex]\[ x(x + 5) = 36 \][/tex]
[tex]\[ x^2 + 5x - 36 = 0 \][/tex]
5. Solve the quadratic equation:
To solve the quadratic equation [tex]\(x^2 + 5x - 36 = 0\)[/tex], we can use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = 5\)[/tex], and [tex]\(c = -36\)[/tex].
Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = 5^2 - 4 \cdot 1 \cdot (-36) \][/tex]
[tex]\[ \Delta = 25 + 144 \][/tex]
[tex]\[ \Delta = 169 \][/tex]
Find the roots:
[tex]\[ x = \frac{-5 \pm \sqrt{169}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-5 \pm 13}{2} \][/tex]
This gives us two solutions:
[tex]\[ x_1 = \frac{-5 + 13}{2} = \frac{8}{2} = 4 \][/tex]
[tex]\[ x_2 = \frac{-5 - 13}{2} = \frac{-18}{2} = -9 \][/tex]
6. Check the solutions:
We must validate that they are within the domain of the original logarithmic function. Logarithms are defined for positive real numbers.
- For [tex]\(x = 4\)[/tex]:
Both [tex]\( \log_6 x = \log_6 4 \)[/tex] and [tex]\( \log_6 (x+5) = \log_6 9 \)[/tex] are defined.
- For [tex]\(x = -9\)[/tex]:
[tex]\(\log_6 (-9)\)[/tex] is not defined because the logarithm of a negative number is not a real number.
7. Identify valid solutions:
From the initial options [tex]\(-12, -9, 4, 32, 36\)[/tex], we see that the valid solution [tex]\(x = 4\)[/tex] is within these options.
### Conclusion:
The potential solution for the equation [tex]\(\log_6 x + \log_6 (x+5) = 2\)[/tex] from the given options is:
[tex]\[ x = 4 \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.